A Report of Study on Optimization Strategy of Foreign Trade Supply Chain Management under B2B Model — Taking Pet Products Market as an Example - Yan, Ruonan (Transactions on Economics, Business and Management Research, 2024)
With the rise of people’s consumption level and the change in consumption concept, the pet economy has become an important part of the social economy, and its vigorous development has brought opportunities for enterprises and society. The traditional management framework of the integrated supply chain, bridging suppliers, manufacturers, distributors, and end-users in the pet market, has persistently failed to adapt to the hallmarks of an efficient, swift, and flexible market environment. Furthermore, ineffective inventory management strategies and the complexities introduced by branded enterprises exacerbate the challenges faced by this traditional model in keeping pace with the dynamic nature of the pet market. This requires optimizing supply chain management, especially the possibility of supply chain management based on big data analysis and Internet of Things technology in the era of digital economy. This report reviews the current situation of the pet market, studies the practical obstacles to the optimization and upgrading of supply chain management in the pet market, and draws a conclusion that the supply chain in the pet market can improve its effectiveness and flexibility through optimization and upgrading under the digital economy. At the same time, it also suggests establishing an effective information sharing mechanism, good partnerships, inventory management optimization, and green supply chain branding. Through these suggestions, enterprises in the pet market can effectively optimize and upgrade the supply chain to adapt to the changing market demand.